STRATEGY FOR ACHIEVING INTEGRITY ZONE AT MAKASSAR VOCATIONAL TRAINING AND PRODUCTIVITY CENTER - Burhanuddin, Burhanuddin; Arfiani, Arfiani; Mustaking, Mustaking; Prasodjo, Tunggul (Universitas Padjadjaran, 2023)
This research is a field research with a qualitative approach that aims to determine the implementation of the Makassar BBPVP integrity zone, to determine the supporting and inhibiting factors of the implementation of the Makassar BBPVP integrity zone and to find out the strategy for achieving the Makassar BBPVP integrity zone. Data collection was carried out using interview techniques that refer to six indicators of the implementation of the Integrity Zone, namely change management, management arrangement, management system arrangement, strengthening work accountability, strengthening staffing, and improving the quality of public services. The data analysis technique is to adapt the design model for the construction of integrity zones. The results of this study show that: 1) the implementation of integrity zones seen from six levers criteria, namely change management, implementation of governance, structuring the HR management system, strengthening performance accountability, strengthening supervision and improving the quality of public services has been carried out properly and in accordance with applicable procedures or mechanisms. 2. The strategy to achieve the integrity zone towards WBK/WBBM at BBPVP Makassar has been well implemented, as seen from the six criteria for leveraging the integrity zone achievement strategy, namely Management optimization, Optimization of governance arrangement, HR Management System Arrangement, Optimization of accountability strengthening, Optimization of supervision strengthening, and Optimization of improving the quality of public services